Technology-specific yield analysis of various photovoltaic module technologies under specific real weather conditions - Bogenrieder, Josef; Hüttner, M.; Luchscheider, Philipp; Hauch, Jens; Camus, Christian; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2017)
In the presented paper, we introduce an approach to rate the performance of modules under specific real weather conditions, since solar modules are rated according to standard test conditions which do not give evidence of the performance under real outdoor conditions. Therefore,we categorize the daily weather at a photovoltaic test site into 7 different climatic-day classifications and multiple cloud scenarios. Two different approaches to evaluate the cloud conditions were investigated. Furthermore, we use the developed approach to rate the performance of 8 different commercially available photovoltaic modules that have been installed and measured in Germany. The evaluation shows that module properties (eg, temperature coefficient, spectral response, and mechanical construction) have a major influence on the performance of photovoltaic modules under different weather conditions.
Keywords: climate; outdoor; performance; photovoltaics; weather; yield analysis